51.9k views
5 votes
Algebra help please !

Algebra help please !-example-1
User KCK
by
6.2k points

2 Answers

2 votes

Answer:

g(f(0)) = 2

Explanation:

To find g(f(0)), you must first find f(0).

f(x) = 3x + 1

f(0) = 3(0) + 1 = 0 + 1 = 1

Now you input 1 into function g(x).

g(x) = (4x + 2)/3

g(1) = [4(1) + 2]/3

g(1) = [4 + 2]/3

g(1) = 6/3

g(1) = 2

g(f(0)) = 2

User Cherona
by
5.4k points
0 votes

For this case we have the following functions:


f (x) = 3x + 1\\g (x) = \frac {4x + 2} {3}

We must find g (f (x)). So:


g (f (x)) = \frac {4 (3x + 1) +2} {3}\\g (f (x)) = \frac {12x + 4 + 2} {3}\\g (f (x)) = \frac {12x + 6} {3}

Now, with x = 0:


g (f (0)) = \frac {12 (0) +6} {3} = \frac {6} {3} = 2

Answer:

Option B

User Prankul Garg
by
6.0k points